Danggui-Shaoyao-San improves cognitive impairment through inhibiting O-GlcNAc-modification of estrogen α receptor in female db/db mice. (5th December 2021) - Shi, Jing-Jing; Liu, Hao-Fei; Hu, Tian; Gao, Xin; Zhang, Yong-Bin; Li, Wei-Rong; Wang, Qi; Zhang, Shi-Jie; Tang, Dan; Chen, Yun-Bo
Abstract: Ethnopharmacological relevance: The traditional Chinese medicine formula Danggui-Shaoyao-San (DSS) has been reported to show therapeutic effect on dementia. Aim of the study: The present study aims to investigate whether DSS treatment could alleviate diabetes-induced cognitive dysfunction, and explores its neuroprotective mechanism on db/db mice. Materials and methods: The female db/db mice were randomly divided into model group, DSS low-dose group and DSS high-dose group. Homologous female db/m mice were used as the control group. DSS was intragastric administrated for 15 weeks. Glucose tolerance, insulin tolerance, blood glucose and blood lipid levels were measured. Morris water maze was used to measure spatial learning and memory ability in mice. Nissl staining and Tunel staining were used to measure the changes of brain neurons, and ELISA kits were used to measure levels of inflammatory mediators (PGE2, TXB2 and LTB4). The kits detected oxidative stress (MDA, SOD, CAT, GSH-PX), nitrosative stress (NO, iNOS, TNOS) and glucose metabolism (LDH, PK, HK) levels. Western blot and immunofluorescence detected neurotrophic factors (PSD95, BDNF, NGF and SYN), apoptosis (Bcl-2, Bax, Bcl-xl, Caspase-3) and changes of ERα, O-GlcNAc, OGT, OGA levels. Results: Morris water maze results showed that DSS could improve the learning and memory abilities of female db/db mice. Nissl staining showed that DSS could relieve hippocampal neurons damage of db/db mice. In addition, the serological tests showed that DSS could improve the impaired glucose tolerance and insulin resistance, while reduce hyperlipemia in db/db mice. Besides, DSS treatment increased the activities of SOD, GSH-PX, and CAT, and reduced MDA, NO, iNOs, tNOS, PGE2, TXB2 and LTB4 levels. Western blot and immunofluorescence results of PSD95, BDNF, NGF, and SYN showed that DSS could improve the expressions of neurotrophic factors. Meanwhile, Tunel staning and Western blot (Bcl-2, Bax, Bcl-xl, Caspase-3) results indicated that DSS could reduce neuronal apoptosis. Finally, Western blot (ERα, O-GlcNAc, OGA, and OGT) and immunofluorescence (ERα and O-GlcNAc) results indicated that DSS could increase the levels of ERα and OGA, decrease the levels of O-GlcNAc and OGT. Conclusion: DSS alleviate DE might be related to improve the abnormal O-GlcNAc-modification of ERα. Graphical abstract: Image 1 Highlights: ● Diabetic encephalopathy is a cognitive impairment caused by diabetes, and is one of the main complications of diabetes ● Danggui-Shaoyao-San has the effect of treating dementia. ● Estrogen can regulate insulin and glucose levels by combining with estrogen α receptor ● Abnormal O-GlcNAc modification levels are closely related to type 2 diabetes.